Driving knowledge management in criminal analysis: exploring the synergy between organisational culture, knowledge management processes, and artificial intelligence = Impulsar la gestión del conocimiento en el análisis criminal : explorando la sinergia entre la cultura organizativa, los procesos de gestión del conocimiento y la inteligencia artificial = Impulsionando a gestão do conhecimento na análise criminal : explorando a sinergia entre cultura organizacional, processos de gestão do conhecimento e inteligência artificial - Pinzón Rodríguez, Nelson Fabián (Revista Criminalidad, 2024)
Criminal analysis has become increasingly relevant in Colombia, particularly after a 2009 study by the International Criminal Investigative Training Assistance Programme. This study identified a lack of institutional understanding among analysts responsible for managing criminal data, resulting in a fragmented knowledge model. In response, the Criminal Analysis Centre was established in 2015 within INTERPOL and the Directorate of Criminal Investigation of the National Police of Colombia, with a specific focus on the "criminal actor" to address previously unmet needs. Information and knowledge management play a crucial role in criminal intelligence, emphasising the importance of continuous access to documented information and robust data collection capabilities. The Centre, staffed by 79 analysts across four key analytical lines, employs various techniques to study criminal behaviour and communications. Despite technological advancements, significant challenges remain in the timely and effective production of analytical outputs. To overcome these, improvement initiatives have been proposed, targeting organisational, product, and process dimensions. Effective criminal information management is deemed essential for the success of these initiatives, which also require appropriate strategic and budgetary attention. The study examines four hypotheses related to knowledge management maturity—culture, processes, technology, and an integrative hypothesis— evaluating their relevance and impact. The results align with previous research, highlighting the need for advanced technologies and tools to enhance effectiveness at each stage of the process, including collaborative tools and data exploitation techniques. Furthermore, an integrated approach is proposed, combining organisational culture, knowledge management processes, and technological infrastructure. Artificial intelligence is also introduced as an innovative tool for managing info-knowledge, addressing a gap in existing proposals that integrate AI throughout the entire knowledge management cycle and incorporate organisational culture as a key element.